Galanin in an Agnathan: precursor identification and localisation of expression in the brain of the sea lamprey Petromyzon marinus - Sobrido-Cameán, Daniel; Lamanna, Francesco; Kaessmann, Henrik (Frontiers in neuroanatomy, 2019)
Galanin is a neuropeptide that is widely expressed in the mammalian brain, where it regulates many physiological processes, including feeding and nociception. Galanin has been characterized extensively in jawed vertebrates (gnathostomes), but little is known about the galanin system in the most ancient extant vertebrate class, the jawless vertebrates or agnathans. Here, we identified and cloned a cDNA encoding the sea lamprey (Petromyzon marinus) galanin precursor (PmGalP). Sequence analysis revealed that PmGalP gives rise to two neuropeptides that are similar to gnathostome galanins and galanin message-associated peptides. Using mRNA in situ hybridization, the distribution of PmGalP-expressing neurons was mapped in the brain of larval and adult sea lampreys. This revealed PmGalP-expressing neurons in the septum, preoptic region, striatum, hypothalamus, prethalamus, and displaced cells in lateral areas of the telencephalon and diencephalon. In adults, the laterally migrated PmGalP-expressing neurons are observed in an area that extends from the ventral pallium to the lateral hypothalamus and prethalamus. The striatal and laterally migrated PmGalP-expressing cells of the telencephalon were not observed in larvae. Comparison with studies on jawed vertebrates reveals that the presence of septal and hypothalamic galanin-expressing neuronal populations is highly conserved in vertebrates. However, compared to mammals, there is a more restricted pattern of expression of the galanin transcript in the brain of lampreys. This work provides important new information on the early evolution of the galanin system in vertebrates and provides a genetic and neuroanatomical basis for functional analyses of the galanin system in lampreys.
Gesehen am 28.10.2019